1998
DOI: 10.1002/(sici)1096-9071(199808)55:4<268::aid-jmv3>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Human cytomegalovirus infection induces mRNA expression and secretion of plasminogen inhibitor type-1 in endothelial cells

Abstract: The aim of the study was to investigate whether infection of endothelial cells with human cytomegalovirus (HCMV) perturbs expression and production of plasminogen activator inhibitor type-1 (PAI-1). mRNA expression of PAI-1 was investigated by isolating total RNA from HCMV-infected and control cells, followed by Northern blotting and probing with 32P-labelled PAI-1 probe. Sandwich ELISA was used to investigate PAI-1 production. HCMV induced the expression of PAI-1-mRNA at 2-5 days postinfection (maximum expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…There are two mechanisms to consider here. Firstly, increased levels of plasminogen activator inhibitor‐1 have been found in influenza, SARS, VZV, CMV, dengue, and HIV infections [Woodroffe and Kuan, 1998; Kurugol et al, 2000; Koppel et al, 2002; Wills et al, 2002; Klein et al, 2005; Keller et al, 2006; Wu et al, 2006; Sosothikul et al, 2007; Schouten et al, 2010]. In HIV infection, elevated plasminogen activator inhibitor‐1 levels have been shown to be related to the metabolic syndrome and the use of protease inhibitors as part of the antiretroviral therapy [Koppel et al, 2002].…”
Section: Methodsmentioning
confidence: 99%
“…There are two mechanisms to consider here. Firstly, increased levels of plasminogen activator inhibitor‐1 have been found in influenza, SARS, VZV, CMV, dengue, and HIV infections [Woodroffe and Kuan, 1998; Kurugol et al, 2000; Koppel et al, 2002; Wills et al, 2002; Klein et al, 2005; Keller et al, 2006; Wu et al, 2006; Sosothikul et al, 2007; Schouten et al, 2010]. In HIV infection, elevated plasminogen activator inhibitor‐1 levels have been shown to be related to the metabolic syndrome and the use of protease inhibitors as part of the antiretroviral therapy [Koppel et al, 2002].…”
Section: Methodsmentioning
confidence: 99%
“…While, most early infections are bacterial in nature, disseminated opportunistic viruses, such as cytomegalovirus (CMV), may present with multi‐organ dysfunction in a fashion that is remarkably similar to systemic bacterial infections (7). In vitro data have shown that CMV affects the endothelium directly, i.e., alteration in clotting time and von Willebrand factor production, secretion of plasminogen inhibitor type 1, factor X and thrombin generation, and adhesion of neutrophils, thus leading to pro‐coagulant and inflammatory states (8–15). Clinical evidence for human endothelial injury by CMV is demonstrated by the microvascular involvement in gastro‐intestinal (colitis), cutaneous (purpura), and hematological (thrombotic microangiopathy) diseases (16–22).…”
mentioning
confidence: 99%